2008
DOI: 10.1111/j.1600-9657.2007.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treated and untreated dental injuries on the quality of life of Ontario school children

Abstract: A population-based, matched case-comparison study was undertaken in 30 schools in two Ontario communities to measure the impact of dental trauma on quality of life (QoL) in Canadian school children. Dental hygienists screened 2422 children aged 12-14 years using the dental trauma index, the decayed, missing and filled teeth index (DMFT) and the aesthetic component of the index of orthodontic treatment needs (AC-IOTN). Cases (n = 135) were children with evidence of previous dental trauma. Controls (n = 135) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
5
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(190 citation statements)
references
References 9 publications
12
147
5
21
Order By: Relevance
“…Children with untreated trauma reported statistically significantly greater difficulty in chewing, social contacts and smiling compared to uninjured children. Children who had been injured but treated reported only the difficulties in chewing, without any effect on their psychological state [16]. The impact of injury to the upper central incisors on the social welfare of children was greater than the functional and psychological well-being in children 12-14 years old.…”
Section: Social and Psychological Consequences Of Dental Trauma In Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with untreated trauma reported statistically significantly greater difficulty in chewing, social contacts and smiling compared to uninjured children. Children who had been injured but treated reported only the difficulties in chewing, without any effect on their psychological state [16]. The impact of injury to the upper central incisors on the social welfare of children was greater than the functional and psychological well-being in children 12-14 years old.…”
Section: Social and Psychological Consequences Of Dental Trauma In Chmentioning
confidence: 99%
“…The appearance of the teeth and dental problems associated with dental injuries may affect the psychological and social well-being of children and downgrade their quality of life. Especially, dental trauma left untreated is more likely to have an impact on children's everyday life than a treated one [16]. …”
Section: Social and Psychological Consequences Of Dental Trauma In Chmentioning
confidence: 99%
“…27 These findings are also consistent with previous research which has identified a number of different visible dental differences (eg malocclusion, dental trauma, severe fluorosis and hypodontia) that are associated with worse OHRQoL in children. 9,11,12,14,15,29,30 Of the OHRQoL domains, it was the impact on emotional and social well-being that was most noticeable. Again, this is consistent with earlier findings which suggest poor dental aesthetics may have a number of psychosocial impacts on children's OHRQoL.…”
Section: Findings In Relation To Oral Health-related Quality Of Lifementioning
confidence: 99%
“…The US Surgeon General’s report on oral health identified sports participation as one of the leading causes of oral and dental injuries (US Department of Health and Human Services, 2000), and previous studies have found that sporting activities account for up to one-third of all dental injuries (ADA Council on Access & ADA Council on Scientific Affairs, 2006; Borssen & Holm, 1997; Lephart & Fu, 1991; US Department of Health and Human Services, 2000). While the rate of dental injuries may be low compared to other common sports-related injuries like sprains and strains, dental injuries can have a long-term functional, social, psychological, and financial impact (ADA Council on Access & ADA Council on Scientific Affairs, 2006; Fakhruddin, Lawrence, Kenny, & Locker, 2008; Newsome et al, 2001). …”
Section: Introductionmentioning
confidence: 99%